Novel phenanthroline–diaryldiazadiene ligands with heteroditopic coordination spheres1. Issue 35 (21st September 2015) - Sorsche, Dieter; Pehlken, Christian; Baur, Christian; Rommel, Sebastian; Kastner, Katharina; Streb, Carsten; Rau, Sven
<x xml:space="preserve">Abstract</x> Twisted and colorful: the two first derivatives of the potential N4 bridging ligand scaffold 1, 10-phenanthroline-5, 6-diaryldiazadiene and a first, selectively phenanthroline coordinated iridium(iii) complex present themselves with distinct electronic and structural peculiarities.